Six-year trajectories of post-traumatic stress and severe psychological distress symptoms and associations with timing of trauma exposure, ongoing adversity and sense of injustice: a latent transition analysis of a community cohort in conflict-affected Timor-Leste. Issue 2 (23rd February 2016) - Tay, AK; Rees, S; Steel, Z; Tam, N; Soares, Z; Soares, C; Silove, DM
Abstract : Objectives: To identify the 6-year trajectories of post-traumatic stress symptoms (PTSS) and psychological distress symptoms, and examine for associations with timing of trauma exposure, ongoing adversity and with the sense of injustice in conflict-affected Timor-Leste. Setting: A whole-of-household survey was conducted in 2004 and 2010 in Dili, the capital of Timor-Leste. Participants: 1022 adults were followed up over 6 years (retention rate 84.5%). Interviews were conducted by field workers applying measures of traumatic events (TEs), ongoing adversity, a sense of injustice, PTS symptoms and psychological distress. Results: Latent transition analysis supported a 3-class longitudinal model (psychological distress, comorbid symptoms and low symptoms). We derived 4 composite trajectories comprising recovery (20.8%), a persisting morbidity trajectory (7.2%), an incident trajectory (37.2%) and a low-symptom trajectory (34.7%). Compared with the low-symptom trajectory, the persistent and incident trajectories reported greater stress arising from poverty and family conflict, higher TE exposure for 2 historical periods, and a sense of injustice for 2 historical periods. The persistent trajectory was unique in reporting greater TE exposure in the Indonesian occupation, whereas the incident trajectory reported greater TE exposure during the later internal conflict that occurred between baseline and follow-up. Compared with the low-symptom trajectory, the incident trajectory reported a greater sense of injustice relating to the periods of the Indonesian occupation and independence. The persistent trajectory was characterised by a sense of injustice relating to the internal conflict and contemporary times. The recovery trajectory was characterised by the absence of these risk factors, the only difference from the low-symptom trajectory being that the former reported a sense of injustice for the period surrounding independence. Conclusions: Our findings suggest that the timing of both TE exposure and the focus of a sense of injustice may differentiate those with persisting and new-onset mental health morbidity in settings of recurrent conflict.